Update on neural network parton distributions: NNPDF1.1 - Rojo, J; Ball, R; De lDebbio, L; Forte, S; Guffanti, A; Latorre, J; Piccione, A; Ubiali, M (2012)
We present recent progress within the NNPDF parton analysis framework. After a brief review of the results from the DIS NNPDF analysis, NNPDF1.0, we discuss results from an updated analysis with independent parametrizations for the strange and anti-strange distributions, denoted by NNPDF1.1. We examine the phenomenological implications of this improved analysis for the strange PDFs.